The Importance of Attention Diversity and How to Measure It. Issue 2 (May 2014) - Boydstun, Amber E.; Bevan, Shaun; Thomas, Herschel F.
<x xml:space="preserve">Abstract</x> Studies of political attention often focus on attention to a single issue, such as front‐page coverage of the economy. However, examining attention to a single issue without accounting for the agenda as a whole can lead to faulty assumptions. One solution is to consider the diversity of attention; that is, how narrowly or widely attention is distributed across items (e.g., issues on an agenda or, at a lower level, frames in an issue debate). Attention diversity is an important variable in its own right, offering insight into how agendas vary in their accessibility to policy problems and perspectives. Yet despite the importance of attention diversity, we lack a standard for how best to measure it. This paper focuses on the four most commonly used measures: the inverse Herfindahl Index, Shannon's H, and their normalized versions. We discuss the purposes of these measures and compare them through simulations and using three real‐world datasets. We conclude that both Shannon's H and its normalized form are better measures, minimizing the danger of spurious findings that could result from the less sensitive Herfindahl measures. The choice between the Shannon's H measures should be made based on whether variance in the total number of possible items (e.g., issues) is meaningful.